Volcanoes to vugs: Demonstrating a FAIR geochemistry framework with a diverse application of major and trace element data through the AuScope EarthBank platform - Nixon, Angus L.; Boone, Samuel C.; Gréau, Yoann; Kohlmann, Fabian; Theile, Moritz; Noble, Wayne; Prent, Alexander; Foden, John; Barnes, Steven; Wainwright, Ashlea N.; Wade, Benjamin; Goemann, Karsten; et al. (Chemical geology, 2025)
Major, minor and trace geochemistry is perhaps the most commonly collected form of analytical data within the Earth sciences, either as the sole approach to a research question or to supplement other methods such as geochronology, thermochronology or isotopic studies. With increasing access to instrumentation and diversification of research applications, inorganic geochemistry data is being produced in volumes which exceed the capacity of existing data management systems, reducing the ability of data to be found, accessed and reused as part of the data lifecycle, thus consigning much data as ‘single use’. Lack of visibility additionally removes the ability to critically assess data quality and validity of interpretations, which is vital for maintaining a healthy research ecosystem. Here we propose a new, flexible inorganic geochemistry reporting schema available within the open access EarthBank platform, as a service to store, interpret, disseminate and explore geochemistry data. The application of this data structure, augmented by purpose-built data interrogation tools, is demonstrated using real-world case studies, including volcanic evolution and magma genesis, mineralisation prospectivity, and catchment provenance and contamination through stream sediment geochemistry. The combination of data schema and integrated data analytics through EarthBank offers a service beyond a basic repository, and allows for active exploration and interpretation of in-house and community geochemistry data, providing a resource beneficial across the entire data lifespan, from generation to publication and reuse. •EarthBank is a free online platform to store and visualise geochemistry data.•Provides new open schema and resources for geochemical data management.•Visualisation and synthesis tools allow investigation of user and published data.•Demonstrated using volcanic arc, Ni-Cu-PGE mineralisation and stream sediment data.